The analysis of Reservoar Porosity Calculation based on Well Log in Bintuni Basin Area - Muhammad Thariq Almuqtadir; Suwondo Suwondo; Warto Utomo; Tati Zera (Journal of Natural Sciences and Mathematics Research, 2022)
The  Bintuni Basin is one of several  oil and gas producing basin in Eastern Indonesia.  This basin has one of the hydrocarbon-producing reservoir in the Kais Formation. The carbonate reservoir in Kais Formation is Middle to Upper Miocene age. The understanding of reservoirs is important for further field development. Petrophysical analysis is a method for understanding reservoirs especially  porosity parameter and estimation of hydrocarbon reserve. The data used in study is  well data including, mudlog report, well report, Gamma Ray (GR), Sonic, Resistivity (ILD, ILS, MSFL), density (RHOB) and NPHI logs. The aim study is to analyze the reservoir using Gamma Ray log and porosity calculation using Sonic, RHOB and NPHI logs. The study method includes regional geological literature review, marker analysis, Gamma Ray picking, and reservoir porosity calculations. According to Gamma Ray picking analysis, the Kais Formation GR has values of  GRsand = 25 API and values of GRshale = 80 API. The Low Gamma Ray  below 60 API is interpretated as carbonate reservoir. For porosity validation, the porosity of routine core analysis (RCAL) data is plotted into porosity logs (porosity calculation using Sonic, RHOB and NPHI logs). Based on the porosity calculation using three porosity logs(Sonic, Density, NPHI Logs), the porosity estimated from density log is more match with the porosity of routine core analysis (RCAL) data. According to porosity calculation at WTU Well, the porosity from log density in the Kais Formation has value from 2% - 25%. The porosity in Carbonate  has large value  as a result of secondary porosity.©2022 JNSMR UIN Walisongo. All rights reserved.